Effect of the Metal of a Metallic Ionic Liquid (-Butyl-Methylimidazolium Tetrachloroferrate) on the Oxidation of Hydrazine - Aguirre-Quintana, M; Aguirre-Quintana, M; Navarro-Gajardo, F; Navarro-Gajardo, F (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
This work investigates the electrocatalytic properties of carbon paste electrodes (CPEs) modified with ionic liquids (IL) and metallic ionic liquid (ILFe) for the hydrazine oxidation reaction (HzOR). The results indicate that ILFe significantly enhances the catalytic activity of the electrode, exhibiting catalysis towards hydrazine oxidation, reducing overpotential, and increasing reaction current. It is determined that the HzOR on the MWCNT/MO/ILFe electrode involves the transfer of four electrons, with high selectivity for nitrogen formation. Additionally, ILFe is observed to improve the wettability of the electrode surface, increasing its capacitance and reaction efficiency. This study highlights the advantages of ILFe-modified CPEs in terms of simplicity, cost-effectiveness, and improved performance for electrochemical applications, demonstrating how the ionic liquid catalyzes hydrazine oxidation despite its lower conductivity. © 2024 by the authors.